2001
DOI: 10.1097/00007632-200102010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Cauda Equina Syndrome Secondary to Idiopathic Spinal Epidural Lipomatosis

Abstract: Spinal epidural lipomatosis can be a cause of back pain but rarely radicular impingement. Magnetic resonance imaging is the procedure of choice. The treatment must be performed early by wide surgical decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 8 publications
1
43
0
5
Order By: Relevance
“…But the significant existence of obesity in advanced lipomatosis cases was not determined yet. Maillot et al [13] claimed that epidural lipomatosis can be especially found in cases with central adiposity, lipid metabolism abnormalities and insulin resistance in their case report. It is stated that central fat distribution is a common characteristic in all cases of epidural lipomatosis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…But the significant existence of obesity in advanced lipomatosis cases was not determined yet. Maillot et al [13] claimed that epidural lipomatosis can be especially found in cases with central adiposity, lipid metabolism abnormalities and insulin resistance in their case report. It is stated that central fat distribution is a common characteristic in all cases of epidural lipomatosis.…”
Section: Discussionmentioning
confidence: 94%
“…It is stated that central fat distribution is a common characteristic in all cases of epidural lipomatosis. The described obesity phenotype is also characteristic of Cushing disease or in long-term glucocorticoid treatment [13].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The symptoms of epidural lipomatosis are not specific and usually include low back pain, sometimes associated with neurological signs, i.e. radicular pain and cauda equina syndrome [7]. Radicular claudication in our patient was confused with signs of arteriopathy, which might have delayed diagnosis.…”
Section: Discussionmentioning
confidence: 70%